Long‐Term Outcomes in Patients With Mixed Aortic Valve Disease and Preserved Left Ventricular Ejection Fraction. Issue 7 (9th April 2020) - Isaza, Nicolas; Desai, Milind Y.; Kapadia, Samir R.; Krishnaswamy, Amar; Rodriguez, L. Leonardo; Grimm, Richard A.; Conic, Julijana Z.; Saijo, Yoshihito; Roselli, Eric E.; Gillinov, A. Marc; Johnston, Douglas R.; Svensson, Lars G.; et al.
Abstract : Background: Concurrent presence of aortic stenosis and aortic regurgitation is termed mixed aortic valve disease (MAVD). Although multiple articles have addressed patients with "isolated" aortic stenosis or aortic regurgitation, the natural history, impact, and outcomes of MAVD are not well defined. Here, we evaluate long‐term outcomes in patients with MAVD and cardiovascular adaptations to chronic MAVD. Methods and Results: This observational cohort study evaluated 862 adult patients (56.8% male) with preserved left ventricular ejection fraction and at least moderate aortic regurgitation and moderate aortic stenosis. Primary outcome was all‐cause mortality. Subgroup analysis was based on treatment modality (aortic valve replacement [AVR] versus medical management). A regression analysis of longitudinal echocardiographic parameters was performed to assess the natural history of MAVD. Mean age was 68±15 years, and mean left ventricular ejection fraction was 58±5%. At 4.6 years (25th–75th percentile range, 1.0–8.7), 58.6% of patients underwent an AVR and 48.8% patients died. In both unadjusted and adjusted Cox survival analysis, AVR was associated with improved survival (hazard ratio, 0.41; 95% CI, 0.34–0.51, P <0.001). Impact of AVR persisted when stratifying the cohort by symptom status and baseline aortic valve area (log rank, P <0.001 for both) and after propensity‐score matching (hazard ratio, 0.40; 95% CI, 0.32–0.50; P <0.001). In the longitudinal analysis, there were statistically significant changes over time in aortic valve peak gradient ( P <0.001) and aortic valve area ( P <0.001) and only mild increases in left ventricular end‐diastolic ( P <0.007) and ‐systolic ( P <0.001) volumes. Conclusions: MAVD confers a high risk of all‐cause mortality. However, AVR significantly reduces this risk independent of aortic valve area, symptom status, and after controlling for confounding variables.